International marketing in an enlarged European Union: Some insights into cultural heterogeneity in Central Europe - Heather Skinner; Krzysztof Kubacki; Gloria Moss; David Chelly (Journal for East European Management Studies, 2008)
We inhabit a global village in which international marketers are encouraged to think and act with both global and local interests in mind. The enlargement of the European Union (EU) in January 2007 has created a 27 member state EU with a population of nearly half a billion. The purpose of this article is therefore to examine the nature of these differences in so far as they impact on the segmentation decisions made by international marketers. This article examines the literature on culture, identity, and self-concept and presents empirical results showing the diversity of these concepts within three countries that are now full EU members - the Czech Republic, Hungary and Poland. – – Wir bewohnen ein globales Dorf, in dem internationale Verkäufer dazu ermuntert werden in globalem und lokalem Interesse zu denken und zu handeln. Die Erweiterung der Europäischen Union im Januar 2007 hat einen Wirtschaftsraum mit 27 Mitgliedstaaten und einer Bevölkerung von fast einer halben Milliarde geschaffen. Die Absicht dieses Artikels ist es deshalb, die Natur dieser Unterschiede zu untersuchen, insofern sie auf die Marktsegmentations-Entscheidungen der Verkaufs-Experten einwirken. Der Artikel untersucht die Literatur bezüglich Kultur, Identität und Selbstkonzept und präsentiert empirische Ergebnisse, die die Ungleichheit dieser Konzepte innerhalb von drei Ländern - Tschechien, Ungarn und Polen - aufzeigen.
Keywords: 650; International Marketing; segmentation; EU enlargement; identity